Search for Potential Vaccine Candidate Open Reading Frames in the Bacillus anthracis Virulence Plasmid pXO1: In Silico and In Vitro Screening - Ariel, N. (American Society for Microbiology, 2002)
A genomic analysis of the Bacillus anthracis virulence plasmid pXO1, aimed at identifying potential vaccine candidates and virulence-related genes, was carried out. The 143 previously defined open reading frames (ORFs) (R. T. Okinaka, K. Cloud, O. Hampton, A. R. Hoffmaster, K. K. Hill, P. Keim, T. M. Koehler, G. Lamke, S. Kumano, J. Mahillon, D. Manter, Y. Martinez, D. Ricke, R. Svensson, and P. J. Jackson, J. Bacteriol. 181:6509-6515, 1999) were subjected to extensive sequence similarity searches (with the nonredundant and unfinished microbial genome databases), as well as motif, cellular location, and domain analyses. A comparative genomics analysis was conducted with the related genomes of Bacillus subtilis, Bacillus halodurans, and Bacillus cereus and the pBtoxis plasmid of Bacillus thuringiensis var. israeliensis. As a result, the percentage of ORFs with clues about their functions increased from ∼30% (as previously reported) to more than 60%. The bioinformatics analysis permitted identification of novel genes with putative relevance for pathogenesis and virulence. Based on our analyses, 11 putative proteins were chosen as targets for functional genomics studies. A rapid and efficient functional screening method was developed, in which PCR-amplified full-length linear DNA products of the selected ORFs were transcribed and directly translated in vitro and their immunogenicities were assessed on the basis of their reactivities with hyperimmune anti-B. anthracis antisera. Of the 11 ORFs selected for analysis, 9 were successfully expressed as full-length polypeptides, and 3 of these were found to be antigenic and to have immunogenic potential. The latter ORFs are currently being evaluated to determine their vaccine potential.